A UPLC‐MS/MS method for simultaneous quantitation of three monoterpene glycosides and four alkaloids in rat plasma: application to a comparative pharmacokinetic study of Huo Luo Xiao Ling Dan and single herb extract. (18th February 2015) - Ai, Yu; Wu, Yun; Wang, Fenrong; Ma, Wen; Bian, Qiaoxia; Lee, David Y.‐W.; Dai, Ronghua
Abstract : The objective of this study was to develop a sensitive and reliable ultra performance liquid chromatography‐tandem mass spectrometry (UPLC‐MS/MS) method for simultaneous quantitation of three monoterpene glycosides (paeoniflorin, alibiflorin and oxypaeoniflorin) and four alkaloids (tetrahydropalmatine, corydaline, dehydrocorydaline and berberine), the main active ingredients of Radix Paeoniae Rubra extract (RPE) and Corydalis yanhusuo extract (CYE) in Huo Luo Xiao Ling Dan (HLXLD), and to compare the pharmacokinetics of these active ingredients in normal and arthritic rats orally administrated with HLXLD or RPE/CYE alone. The analytes and internal standard (IS) (geniposide) were separated on a XBridge C18 column (150 × 4.6 mm, 3.5 µm) using gradient elution with the mobile phase consisting of methanol and 0.01% formic acid in water at a flow rate of 0.6 ml/min. The detection of the analytes was performed on Acquity UPLC‐MS/MS system with an electrospray ionization and multiple reaction monitoring mode via polarity switching between negative (for monoterpene glycosides) and positive (for alkaloids) ionization mode. The lower limits of quantification were 2.5, 1, 0.5, 0.2, 0.2, 0.02 and 0.01 ng/ml for paeoniflorin, alibiflorin, oxypaeoniflorin, tetrahydropalmatine, corydaline, dehydrocorydaline and berberine, respectively. Intra‐day and inter‐day precision and accuracy of analytes were well within acceptance criteria (15%). The mean extraction recoveries of analytes and IS from rat plasma were all more than 83.1%. The validated method has been successfully applied to determination of the analytes. Results showed that there were remarkable differences in pharmacokinetic properties of the analytes between herbal formula and single herb group, normal and arthritic group. Copyright © 2015 John Wiley & Sons, Ltd.